NiFeRu Layered Double Hydroxide and Its Derivatives Supported on Graphite Foam as Binder-Free Cathode for Nonaqueous Li-O2 Batteries - Song, Ming; Tan, Hua; Tian, Lin; Li, Jing; Xu, Yan; Shi, Liluo; Sun, Limei; Zhuang, Wenchang; Du, Xihua (Frontiers in Energy Research, 2020)
Li-O2 batteries (LOBs) generally referred as Li-air batteries (LABs) potentially have a high specific capacity among all kinds of metal-ion batteries. However, it suffers severely from sluggish discharge/charge kinetics. A binder-free integrated cathode is fabricated which contains NiFeRu layered double hydroxide (NiFeRu LDH) nanosheets grown on a 3D conductive graphite foam (NiFeRu LDH@GF) in this work. This integrated 3D cathode exhibits a specific capacity of 3,085 mAh g−1 and a cycle life of 46. The electrochemical performances of NiFeRu LDH derived metal oxides (DMO@GF) by calcining NiFeRu LDH@GF at 350°C, 450°C, and 550°C are also been investigated. The 450°C obtained DMO@GF (450-DMO@GF) exhibits the highest catalytic activity for oxygen reduction/evolution reaction. The unique floccule-like and cross-connected structure of the 450-DMO@GF and its low charge transfer resistance are responsible for the outstanding electrochemical performance.